2017
DOI: 10.1093/cid/cix697
|View full text |Cite
|
Sign up to set email alerts
|

Hematophagous Ectoparasites of Cliff Swallows Invade a Hospital and Feed on Humans

Abstract: We describe a hospital infestation by 2 hematophagous ectoparasites of cliff swallows that nested in the window eaves. Breaks in window seals allowed entry of swallow ticks and swallow bugs. These pests emerged in large numbers in patient rooms, hallways, and stairwells; 17% of the ticks fed on humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Hansel et al [ 22 ] reported a similar case of human infestation by martin bugs ( C. hirundinis ) in Italy. Moreover, other human infestation cases with swallow bugs have been reported in the US and Japan [ 21 , 47 ]. To date, in France, in addition to C. hirundinis we have found two species ( C. hemipterus and C. lectularius ) that bite and feed on human blood [ 5 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hansel et al [ 22 ] reported a similar case of human infestation by martin bugs ( C. hirundinis ) in Italy. Moreover, other human infestation cases with swallow bugs have been reported in the US and Japan [ 21 , 47 ]. To date, in France, in addition to C. hirundinis we have found two species ( C. hemipterus and C. lectularius ) that bite and feed on human blood [ 5 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under certain conditions, C. hirundinis are able to feed on human blood, and their bite is known to be more painful than that of bedbugs [ 6 , 7 , 21 , 22 ]. However, except for experienced entomologists, it is challenging to make a morphological distinction between Cimex spp.…”
Section: Introductionmentioning
confidence: 99%
“…Human infestations with C. hirundinis have also been reported in France and Japan [31,131]. Moreover, the co-occurrence of a hospital infestation with two hematophagous arthropods, Cimex vicarius and Argas cooleyi has been reported in Tucson, Arizona, USA [136]. Cimex vicarius and C. hirundinis are also pests of considerable importance to swallows because they cause nestling mortality due to severe blood loss when infestations are heavy [1].…”
Section: Medical and Veterinary Impact Of Swallow Bugsmentioning
confidence: 99%
“…This species has never before been stated to be a vector of human pathogens. The swallow bug species may serve as an alternative host when their preferred host is absent [136]. A case of occupational human infestation with C. hirundinis in Italy showed that two farm workers sustained papules covered with haemorrhagic crusts on their abdomens and trunks [130].…”
Section: Medical and Veterinary Impact Of Swallow Bugsmentioning
confidence: 99%
“…Similarly, two bat bugs, Cimex insuetus (Ueshima) and Stricticimex parvus (Ueshima), were suspected of carrying and transmitting zoonotic virus to humans [6]. Additionally, the swallow bug, Oeciacus vicarius (Horváth), was reported to invade human interfaces and bite people [7].…”
Section: Introductionmentioning
confidence: 99%